2015
DOI: 10.1890/es14-00528.1
|View full text |Cite
|
Sign up to set email alerts
|

Serpentine ecosystem responses to varying water availability and prescribed fire in the U.S. Mid‐Atlantic region

Abstract: Abstract. Grasslands growing atop serpentine bedrock are subject to edaphic stresses and, as a result, are low productivity ecosystems. Nutrient limitations are so severe in some serpentine grasslands that plant growth is unaffected by increased water availability. However, little is known of how serpentine grasslands in eastern North America function and respond to environmental changes, including variation in water availability. Serpentine barrens of the U.S. Mid-Atlantic region are globally rare ecosystems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Seneviratne et al (2015) found 2.3% total organic carbon in soil from Yudhaganawa serpentine deposit in Sri Lanka, which is similar to the findings of the present study. Moreover, the comparatively low soil water holding capacities observed at saturation point and field capacity are often reflected in serpentine soils worldwide (Schedlbauer 2015). Soil moisture regime directly causes for changes in physicochemical and biological attributes of soil, including pH, electrical conductivity, and organic matter content (Van den Berg and Loch 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Seneviratne et al (2015) found 2.3% total organic carbon in soil from Yudhaganawa serpentine deposit in Sri Lanka, which is similar to the findings of the present study. Moreover, the comparatively low soil water holding capacities observed at saturation point and field capacity are often reflected in serpentine soils worldwide (Schedlbauer 2015). Soil moisture regime directly causes for changes in physicochemical and biological attributes of soil, including pH, electrical conductivity, and organic matter content (Van den Berg and Loch 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The serpentine grasslands themselves present a harsh abiotic filter, most notably containing high levels of toxic heavy metals, which have been found to cause divergence among populations via selection (Anacker, 2014; Brady et al, 2005; Kazakou et al, 2008; Turner et al, 2010) and/or via biased dispersal due to associations with flowering time (Antonovics, 2006; Dittmar & Schemske, 2017; Rajakaruna & Bohm, 1999). Soil characteristics can vary even among serpentine sites within a region, with some presenting harsher conditions than others (Batianoff & Singh, 2001; Schedlbauer, 2015). Thus, the combination of an intervening matrix, composed of a complex mosaic of natural and anthropogenically‐altered lands, with variable soil metal content among serpentine grassland patches presents an apt system to investigate patterns of both IBR and IBE.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of species resulting from eutrophication typically occurs through competitive exclusion (Wassen et al 2005) when there are competitive species present that are able to rapidly exploit the available nutrients and outcompete the resident species that are adapted to low nutrient and often, very stressful conditions. Serpentine systems are usually resistant to colonisation by non-serpentine specialists due to high heavy metal concentrations, low organic matter and free-draining soils, but can be vulnerable to invasion when the normally restrictive growing conditions are ameliorated through increases in nutrients (Huenneke et al, 1990;Vallano, Selmants and Zavaleta, 2012) and/or water availability (Schedlbauer 2015). However, the patterns of response are variable with some invasive species appearing to be N-limited and some P-limited, whilst others only need increased water availability to become established.…”
Section: Introductionmentioning
confidence: 99%